PELATIHAN PENYUSUNAN LABA RUGI DAN NERACA UNTUK SISWA SMA - Jessica Octaviani; Agustin Ekadjaja (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Financial literacy is a fundamental skill that should be developed from an early age, especially in understanding and preparing financial statements. Accounting education at the high school level remains limited to basic theoretical concepts, with insufficient emphasis on the practical preparation of financial reports such as income statements and balance sheets. This training program aimed to enhance the understanding and skills of students at SMA Santo Yakobus in preparing financial statements in a systematic and accurate manner. The training was conducted using a participatory educational approach, consisting of material presentations, interactive discussions, case studies, and exercises in preparing financial reports based on simplified data. The results of the program showed that the training significantly improved students’ understanding of the structure and function of income statements and balance sheets, as well as their ability to independently prepare financial statements. This program demonstrates that training activities can have a positive impact on strengthening financial literacy at the secondary education level. Furthermore, the training is expected to serve as a learning model that can be implemented in other schools as part of the synergy between higher education and secondary education. Literasi keuangan merupakan kemampuan dasar yang penting untuk dimiliki sejak usia sekolah, khususnya dalam memahami dan menyusun laporan keuangan. Pembelajaran akuntansi di tingkat Sekolah Menengah Atas masih terbatas pada konsep dasar, tanpa penekanan yang memadai pada praktik penyusunan laporan keuangan seperti laporan laba rugi dan neraca. Kegiatan Pelatihan ini bertujuan untuk meningkatkan pemahaman dan keterampilan siswa SMA Santo Yakobus dalam menyusun laporan keuangan secara sistematis dan akurat. Metode pelaksanaan kegiatan dilakukan melalui pendekatan edukatif partisipatif, yang terdiri atas pemaparan materi, diskusi interaktif, studi kasus, serta latihan penyusunan laporan keuangan berdasarkan data sederhana. Hasil kegiatan menunjukkan bahwa pelatihan ini mampu meningkatkan pemahaman siswa terhadap struktur dan fungsi laporan laba rugi dan neraca, serta meningkatkan kemampuan siswa dalam menyusun laporan keuangan secara mandiri. Kegiatan ini membuktikan bahwa kegiatan pelatihan yang dilakukan dapat memberikan dampak positif terhadap penguatan literasi keuangan di tingkat pendidikan menengah. Pelatihan ini diharapkan menjadi model pembelajaran yang dapat digunakan di sekolah lain sebagai bagian dari sinergi antara pendidikan tinggi dan pendidikan dasar-menengah.